Constitution : what it means to the people - Kuppuswami, Alladi (Hyderabad, 2000)
This is a collection of essays on various aspects of the Indian Constitution by the distinguished jurist, Justice Alladi Kuppuswami, Chief Justice of Andhra Pradesh (Retd.) Here, the reader will find answers to intriguing questions like : Should Article 356 be repealed? Is it necessary to change over from parliamentary domocracy to a presidential system? Does a government servant have the right to criticize the government? Can conversions be banned? Although some of these questions were thrown up by specific political events, the answers and discussions have a great deal of permanence and will have relevance as long as the Indian Constitution lasts. Even if the Constitution is reviewed, the discussion in these pages will be of great significance to the very review process.
Keywords: Constitutions